1988
DOI: 10.1152/ajpgi.1988.254.1.g1
|View full text |Cite
|
Sign up to set email alerts
|

Biliary catabolism of glutathione and differential reabsorption of its amino acid constituents

Abstract: Biliary excretion of glutathione, free amino acids, and total amino acids (after acid hydrolysis) was measured in hepatic bile collected from guinea pigs, rabbits, and dogs anesthetized with pentobarbital sodium. In controls, the concentration of glutathione in bile was less than 20 microM in all three species. However, when hepatic gamma-glutamyltransferase activity was decreased by retrograde intrabiliary infusion of the irreversible inhibitor acivicin (AT-125; 20 mumol/kg), there was a marked increase in bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…Very little is known about the presence of small peptides in bile fluid. Glutathione is secreted into bile and is almost completely broken down (6). The authors of this study suggested that the resulting products are reabsorbed either as peptides, conjugates, or free amino acids.…”
Section: Discussionmentioning
confidence: 84%
“…Very little is known about the presence of small peptides in bile fluid. Glutathione is secreted into bile and is almost completely broken down (6). The authors of this study suggested that the resulting products are reabsorbed either as peptides, conjugates, or free amino acids.…”
Section: Discussionmentioning
confidence: 84%
“…Previously acivicin has been used to inhibit -GT under in-vivo conditions in the rat kidney (Scott & Curthoys, 1987) and brain (Hill et al, 1985) and during perfusion in bile (Ballatori et al, 1988). These studies have resulted in glutathionuria and an accumulation of tissue GSH with a decrease of free L-glutamic acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione, which is secreted by hepatocytes, is degraded in bile by -glutamyltranspeptidase, an enzyme found abundantly on the canalicular hepatocyte and ductal cholangiocyte apical plasma membranes (116). Functional studies suggest that cholangiocytes absorb biliary glutamate, cysteine, and glycine by Na + -dependent and independent transport mechanisms that are distinct from those in hepatocytes (26,42). Absorption of these amino acids by cholangiocytes may conserve them for glutathione resynthesis and thus be involved in "bile salt-independent" canalicular bile secretion (183); in addition, it may generate osmotic gradients of 3 to 12 mOsm that favor water absorption and thereby be directly involved in ductal bile modification (85).…”
Section: Cholangiocyte Absorptionmentioning
confidence: 99%